Cultural investment of Javanese Krama language in Islamic elementary schools - Khulukul Khuzaefi (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2018)
Language is the most essential communication tool for human beings. Languages possessed by humans are so dynamic that it continues to evolve over time. The language instruction was termed Linguistic Etiquette. In Linguistic Etiquette there is a term of speech levels.  The use of language in Islamic Elementary School (Madrasa Ibtidaiyah/MI) was implemented in an integrated manner with the relationshipbetween fields of study. Javanese is the mother tongue of the Javanese. The society levels of speech in Javanese language are Ngoko, Krama Madya, and Krama Inggil. The Javanese practices Krama level language to communicate between students with teachers, among teachers and teachers with headmaster of MI at school. This research was conducted qualitatively to informants from MI Tegalwaton and MI Al Islam Bonomerto. The researcher used qualitative descriptive approach to describe the state or phenomenon status of the data obtained from the research object, which then analyzed. This study are investigating MI programs in instilling Javanese `Krama` language, the results of Javanese `Krama` language cultural cultivation in MI Tegalwaton and MI Al Islam Bonomerto as well as obstacles experienced by the students in using Javanese `Krama` language.